Evaluation and characterization of pelleted biomass from selected resouces for ethanol production - Theerarattananoon, Karnnalin (Kansas State University, 2012)
Lignocellulosic biomass such as agricultural residues tends to be a sustainable feedstock for production of biofuels and biobased products in the long term due to its high availability and relative low cost. However, conversion of lignocellulosic biomass to biofuels faces significant technical challenges. One of the major challenges is biomass logistics. The agricultural residues are often harvested during a limited harvest season and stored as bales with low bulk density, making them difficult to handle, transport, store, and use in their natural forms. Densification of biomass by pelleting process could significantly improve the bulk density of biomass and thus improve handling efficiency and reduce transportation and handing costs. The main focus of this research was to better understand the impacts of pelleting process as well as pelleting conditions on physical properties, chemical compositions, biomass structure, and fermentable sugar yield of sorghum stalk, corn stover, wheat straw, and big bluestem. Results showed that pelleting process can increase biomass density up to 9-12 folds. Pelleting condition such as hammer mill screen size and ring-die pelleting mill die thickness had significant effects on bulk density, true density, and durability of biomass pellets. Although the pelleting process did not show significant effects on chemical composition of biomass before dilute-acid pretreatment process, glucan content of biomass pellets increased with the increase in ring-die pelleting mill die thickness and decreased with the increase in mill screen size after dilute-acid pretreatment. Opposite trend was observed for xylan content of biomass pellets as affected by pelleting conditions after dilute-acid pretreatment process. Biomass crystallinity increased after pelleting process, but not in a significant level. Softened surface region of biomass was removed after pelleting process, making the biomass more amendable to enzymatic attack. In this study, the optimum pelleting conditions were to grind the biomass feed using a 6.5-mm mill screen and to pellet biomass using a 44.5-mm ring-die pelleting mill die thickness. Under this optimum pelleting condition, the enzymatic conversion of cellulose of wheat straw pellets was the highest (94.1%), followed by corn stover pellet (93.1%), sorghum stalk pellet (92.1%), and big bluestem pellet (91.1%).
Keywords: Biomass pellet; Bioethanol; Enzymatic conversion of cellulose; Biomass structure; Physical properties; Engineering, Agricultural (0539)